PSIV-B-18 Effects of Winter Hair Shedding Level and Service Sire Breed on cow-Calf Performance of a Spring-Calving Herd in the Southeastern United States. (21st September 2022) - Hayes, Emily G; Hurt, Kaylee; Leite-Browning, Maria L; Browning, Richard
Abstract: Over three years, the effects of winter hair shedding and service sire breed on cow-calf performance were assessed. Dexter cows were scored each spring for percentage of winter hair loss (0% = thick coat, 100% = smooth coat). Cows were exposed by natural service to Dexter (DEX) and Mashona (MAS) bulls in July. Calves were weighed at birth, 3.5 mo of age, and at weaning (7 mo). Based on hair scores in early June of each year, cows were classified as low shedders (LoS; 0 to 50%; n = 67) or high shedders (HiS; 51 to 100%; n = 130). Hair shed interacted (p < 0.05) with sire breed to affect pregnancy rates. HiS x MAS had a greater (p < 0.05) pregnancy rate than HiS x DEX (92.8 ± 3.8 vs. 60.9 ± 7.7%). Breeds did not differ (p > 0.05) within LoS. Pregnancy rate was greater (p < 0.05) for HiS than LoS (81.6 ± 4.8 vs. 63.1 ± 7.7%). Hair shed scores did not affect (p > 0.05) ADG. MAS calves had greater (p < 0.05) birth to 3.5 mo and birth to weaning ADG (0.77 ± 0.06 and 0.58 ± 0.05 kg/d, respectively) than DEX calves (0.64 ± 0.06 and 0.48 ± 0.05 kg/d, respectively). Across two complete production years, shedding group and service sire breed interacted (p < 0.05) for calf weight weaned per cow exposed. Within MAS, HiS weaned more weight (p < 0.05) than LoS (157.08 ± 24.27 vs. 48.47 ± 28.90 kg). Hair shedding was not important within DEX. Within HiS, MAS cows weaned more weight (p < 0.05) than DEX cows (157.08 ± 24.27 vs. 84.01 ± 24.01 kg). Service sire breed was not important within LoS. Hair shedding level and service sire breed influenced cow-calf performance.